Empowering the Talempong Traditional Music Community as a Tourism Attraction in West Sumatra - Rina Armeniza Aziz (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
The background of this research is that talempong, a traditional Minangkabau music developed as a cultural tourism instrument, faces challenges in motivating the younger generation to develop and continue the cultural heritage. The purpose of this study is to identify effective community empowerment strategies for talempong as a cultural tourism attraction in West Sumatra. The study used a qualitative approach with ethnographic methods. Data were collected through participant observation, in-depth interviews with community leaders, cultural artists, and local government officials, and documentation studies. The results indicate that Talempong community empowerment is implemented through three main strategies: institutionalization of community organizations, integration of Talempong performances into tourism packages, and capacity development of local artists. The research findings indicate that community empowerment contributes significantly to strengthening local cultural identity, improving the economic well-being of artists, and enhancing the attractiveness of West Sumatra as a cultural tourism destination. This study provides recommendations for local governments and tourism stakeholders to develop policies that support the sustainability of traditional Talempong music as a priceless cultural heritage asset.